2016
DOI: 10.4014/jmb.1512.12036
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Composition in the Marine Sediments of Jeju Island: Next-Generation Sequencing Surveys

Abstract: Marine sediments are a microbial biosphere with an unknown physiology, and the sediments harbor numerous distinct phylogenetic lineages of Bacteria and Archaea that are at present uncultured. In this study, the structure of the archaeal and bacterial communities was investigated in the surface and subsurface sediments of Jeju Island using a next-generation sequencing method. The microbial communities in the surface sediments were distinct from those in the subsurface sediments; the relative abundance of sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 54 publications
(62 reference statements)
5
18
0
1
Order By: Relevance
“…This result corresponds with that of Suh et al [7] who reported that the Proteobacteria was the dominant phylum in seawater from Gosung Bay, South Korea, followed by the Bacteroidetes and Actinobacteria. Similarly, most of the bacterial sequence reads in marine sediments from Jeju Island, South Korea, were also associated with the Proteobacteria and Bacteroidetes, followed by the Actinobacteria, Acidobacteria, and Firmicutes [20].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This result corresponds with that of Suh et al [7] who reported that the Proteobacteria was the dominant phylum in seawater from Gosung Bay, South Korea, followed by the Bacteroidetes and Actinobacteria. Similarly, most of the bacterial sequence reads in marine sediments from Jeju Island, South Korea, were also associated with the Proteobacteria and Bacteroidetes, followed by the Actinobacteria, Acidobacteria, and Firmicutes [20].…”
Section: Discussionmentioning
confidence: 98%
“…Marine environment is the one of the most extensive habitats for microorganisms, covering more than twothirds of the surface of the earth [20]. Marine bacteria play important roles in energy and matter fluxes in the sea [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This use of alternative electron acceptors in turn influences the oxygen-reduction potential at various depths in the sediment. Analysis of sediments from around the world has identified key microbial taxa associated with these redox reactions [ 13 15 ]. The microbial reduction of Fe 3+ and SO 4 2− produces ferrous iron (Fe 2+ ) and toxic H 2 S, respectively, that can subsequently chemically precipitate as iron sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Firmicutes have been associated to diseased specimen of A. aerophoba (Webster, Xavier, et al, 2008) and significantly changed in their relative abundance after transplantation of sponge specimens (Meyer et al, 2016). More commonly however, Clostridia represent dominant members of the microbial communities inhabiting marine sediments (Choi et al, 2016) and might thus be only coincidentally present in sponges at the time of sampling. The spore-forming capabilities of this generally obligate anaerobic lineage (Yutin & Galperin, 2013) probably rendered Clostridia resistant to oxygen during sponge processing and cryopreservation and enabled their growth in the MiniColumns once the oxygen was depleted.…”
Section: What Did We Culturementioning
confidence: 99%